PENGARUH MODEL PEMBELAJARAN INVESTIGASI KELOMPOK TERHADAP KEMAMPUAN PENALARAN MATEMATIKA SISWA PADA POKOK BAHASAN TEOREMA PHYTAGORAS - Rizki Mahriady; Nurdalilah Nurdalilah; Adek Nilasari Harahap (JURNAL MathEdu (Mathematic Education Journal), 2022)
This study aims to determine whether there is a positive and significant effect between the Group Investigation learning model on students' mathematical reasoning abilities in the Pythagorean Theorem subject in class VIII-B MTS YPKS Padangsidimpuan. The population in this study were all eighth grade students at MTS YPKS Padangsidimpuan. The sample of this study consisted of 2 classes of 30 students, namely class VIII-B as the experimental class and class VIII-A as the control class. The experimental class uses the Group Investigation learning model, and the control class uses the Conventional learning model. This type of research is an experiment by giving treatment to the research sample group and then given a pretest and posttest, as a data collection tool. Before testing the hypothesis, first the normality and homogeneity of the test were tested. From the post-test data analysis of reasoning ability using the t-test at level = 0.05, it was obtained that thitung > ttabel was 10.322 > 1.667 so that for both hypothesis tests H0 was rejected and H1 was accepted. It can be concluded that there is a positive and significant influence between the Group Investigation learning model on students' mathematical reasoning abilities.